Study on web applications in learning process among quantity surveying undergraduates - Tan, Chin Keng; Yeoh, Kah Ching (2012)
A web application is an application that utilizes web and [web] browser technologies to accomplish one or more tasks over a network. Some researches uncovered that web applications or web-based tools, if effectively deployed, could enhance students learning experiences. This study aims to examine the awareness, level of usage and perceived usefulness of educational related web applications among Malaysian Quantity Surveying undergraduates. A questionnaire survey was conducted to achieve the objectives of this study. The data for this study were collected from 130 Quantity Surveying undergraduates in Malaysia. The findings reveal that Quantity Surveying undergraduates are generally well exposed to educational related web applications except online portfolio and podcast. They have high usage on web search, social network website, email, course website and web translator. The top three most useful web applications in their learning process are web search, social network website and online storage.